Strategic Group of Indonesia Retail Industry - Luki Ramdani; A.Fadel Muhammad; Popy Rufaidah (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This research aims to produce a strategic group map of the retail industry in Indonesia at PT Sumber Alfaria Trijaya Tbk. A strategic group is a collection of companies in an industry with similarities in strategy implementation, the scope of operations, and the resources they use to win the competition. The research method used is the case study method, namely a series of scientific activities carried out in detail and depth to reveal an event and activity of an entity in order to gain in-depth knowledge about the event. This study explores strategic groups in the retail industry concerning the position of PT Sumber Alfaria Trijaya Tbk as one of the retail business players, including the supermarket and minimarket sub-sectors. The results of the study show a mapping of strategic groups in the retail industry in Indonesia using indicators of wide geographical coverage and the number of outlets owned by companies in the industry. The strategic group mapping of the Indonesian retail industry consists of sub-sectors: supermarkets and minimarkets (such as PT. Sumber Alfaria Trijaya Tbk), retail electronics (such as PT. Erajaya Swasembada Tbk); retail automotive (e.g., PT. Mitra Pinasthika Mustika Tbk); retail clothing and textiles (e.g., PT MapActivs Adiperkasa Tbk; and PT Mitra Adiperkasa Tbk).